The Role of Mindfulness in Enhancing Mental Health and Psychological Well-Being Among Adolescents: A Literature Review - Nurhillal Bestari; Amirah Diniaty (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Adolescent mental health has become an increasingly important global issue due to the rising prevalence of anxiety, depression, psychological stress, and various emotional disorders that affect adolescents’ social development, academic performance, and overall quality of life. This condition highlights the urgent need for effective, preventive, and accessible psychological interventions, one of which is mindfulness. This study aims to analyze the role of mindfulness in improving adolescent mental health and psychological well-being by identifying the effectiveness of interventions, factors influencing program success, and their contributions to adolescent mental health development. The study employed a descriptive qualitative approach using a library research design in the form of a narrative literature review of relevant national and international scientific articles concerning mindfulness and adolescent mental health. The findings indicate that mindfulness-based interventions (MBIs) generally reduce anxiety, depression, and stress while improving emotional regulation, attention, psychological well-being, and sense of meaning in life among adolescents. The effectiveness of mindfulness is influenced by intervention duration, implementation quality, participant characteristics, intervention settings, and individual engagement in mindfulness practices. However, several studies reported inconsistent findings, particularly regarding long-term effects and universal school-based implementation. This study concludes that mindfulness has significant potential as a preventive and promotive approach to supporting adolescent mental health and may serve as a foundation for developing more adaptive, holistic, and evidence-based psychological interventions.